2021
DOI: 10.3390/ijerph19010184
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Anxiety and Stress on Caregivers of Persons with Dementia (CGPWD) in Hong Kong amid COVID-19 Pandemic

Abstract: Background: Coronavirus disease 2019 (COVID-19) contributed to increasing prevalence of depressive symptoms and other psychological repercussions, particularly in the disease population in Hong Kong. Nonetheless, the caregiver burden of caregivers of persons with dementia (CGPWD), has been under-investigated. Aims: This study examined the psychological impact and its correlates on the CGPWD in Hong Kong amid the COVID-19 outbreak. Methods: CGPWD referred from rehabilitation clinics and online seminar were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…The anxiety of family caregivers limits their capacity to help the patient and can also exacerbate the patient's anxiety [ 13 ]. Nonetheless, home caregivers of the COVID-19 patients are experiencing greater levels of stress, anxiety, and depression symptoms [ 14 , 15 ] for a variety of reasons, including the fear of infection or transmitting it to others, poor community and governmental support, lack of access to medical care, and stigma [ 16 ]. These family caregivers would also face critical challenges compared to other caregivers because of the limited training and resources at hand as well as their insufficient knowledge about this emergent disease [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The anxiety of family caregivers limits their capacity to help the patient and can also exacerbate the patient's anxiety [ 13 ]. Nonetheless, home caregivers of the COVID-19 patients are experiencing greater levels of stress, anxiety, and depression symptoms [ 14 , 15 ] for a variety of reasons, including the fear of infection or transmitting it to others, poor community and governmental support, lack of access to medical care, and stigma [ 16 ]. These family caregivers would also face critical challenges compared to other caregivers because of the limited training and resources at hand as well as their insufficient knowledge about this emergent disease [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Major depressive disorder (MDD) is a disabling mental disorder characterized by depressed mood, loss of interest, and reduced drive, and it is the most prevalent, affecting approximately 15-17% of the population and showing a high suicide risk rate equivalent to around 15% (1). Recently, there have been lots of work testing the association between COVID-19 and depression in the global general populations and vulnerable subpopulations (2)(3)(4)(5). One study suggested that the COVID-19 pandemic accelerates the increase in depressive symptoms from 19.8% in the months prior to the pandemic to 40.4% during the pandemic (6).…”
Section: Introductionmentioning
confidence: 99%
“…This problem can lead to the dissolution of a family [ 10 ]. From this perspective, several existing studies have described the relationship between the care burden and depression of various types of family caregivers by using the Center for Epidemiology Studies Depression Scale (CES-D) [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Family-caregiver characteristics, such as perceptions of spousal relationships, health problems, and care time and cost, were associated with depression [ 13 ]. In a study of 51 caregivers of dementia patients, approximately 64.7% of participants showed depressive symptoms (CES-D score ≥ 16), and these symptoms increased significantly during the 3-month follow-up period [ 14 ]. A study on the depression of caregivers of stroke survivors demonstrated that the relationship with the patient, the burden of “care”, and depression had a significant effect on their quality of life [ 11 ].…”
Section: Introductionmentioning
confidence: 99%